(untitled) (Research, Society and Development, 2021)
Netherton Syndrome (NS) is a very rare and severe dermatosis, characterized by reddened skin with abundant desquamation, generating rapid skin regeneration and causing fluid loss. Diagnosis is challenging and can often be confused with other comorbidities. NS has no cure, only treatment. The pharmaceutical care of this disease helps to improve the patient’s quality of life, as well as better adaptation to treatment. This work aims to survey, based on the current literature, the characteristics of SN, to facilitate the diagnosis; demonstrate its various forms of treatment; analyze the role of the pharmacist to improve the quality of life of the carrier. For this investigation, a bibliographic research was adopted, based on a literature review of scientific articles available in the electronic database of the Scientic Electronic Library Online (SciELO) and Medical Literature Analysis And Retrieval System Online (MEDLINE). In the reviewed bibliographies it was possible to find that NS is caused by genetic mutation, it has a complex diagnosis, and bullous ichthyosis, atopic dermatitis, among others, can be confused. Some of the treatments are used emollients, reducing transepidermal water loss, dupilumab is also used, a biological medication of human monoclonal IgG4 antibody, improving the condition of the skin, as well as pharmaceutical care in this scenario brings great improvements in adherence to treatment. It is noticed that there is still a lot of study to be carried out and to be able to further improve the well-being of these individuals, as well as more research on the syndrome in order to make a quick diagnosis and effective treatments possible.